An LMI Approach for Dynamics of Switched Cellular Neural Networks with Mixed Delays. (15th April 2013) - Huang, Chuangxia; Kuang, Hanfeng; Chen, Xiaohong; Wen, Fenghua
Abstract : This paper considers the dynamics of switched cellular neural networks (CNNs) with mixed delays. With the help of the Lyapnnov function combined with the average dwell time method and linear matrix inequalities (LMIs) technique, some novel sufficient conditions on the issue of the uniformly ultimate boundedness, the existence of an attractor, and the globally exponential stability for CNN are given. The provided conditions are expressed in terms of LMI, which can be easily checked by the effective LMI toolbox in Matlab in practice.